2019
DOI: 10.1108/ijhrh-02-2018-0015
|View full text |Cite
|
Sign up to set email alerts
|

Emotional empathy mediates the relationship between personality traits and coping strategies in orphan and non-orphan students

Abstract: Purpose The purpose of this paper is to inspect the potential mediation pathways among emotional empathy, personality traits and coping strategies in orphan and non-orphan students. Additionally, it designed to investigate the association of coping strategies with emotional empathy and personality traits. Design/methodology/approach Purposive sampling technique and cross-sectional design were employed in current study. The data of 130 adolescents (institutionalized orphans, n= 62; school students, n=68) were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 53 publications
(76 reference statements)
1
4
0
Order By: Relevance
“…It is hypothesized that orphans may demonstrate higher compassion scores than nonorphans because of their living context where orphans live and form friendships with a diverse pool of peers. This finding is also consistent with previous research that found higher levels of emotional empathy among orphans in comparison to non-orphans [ 71 ]. The lack of differences in other dimensions of Utu by gender and orphan study resonate with the philosophical underpinnings of Utu that holds humanness as essential and protected irrespective gender, race, tribal, religious or political affiliations [ 72 ].…”
Section: Discussionsupporting
confidence: 93%
“…It is hypothesized that orphans may demonstrate higher compassion scores than nonorphans because of their living context where orphans live and form friendships with a diverse pool of peers. This finding is also consistent with previous research that found higher levels of emotional empathy among orphans in comparison to non-orphans [ 71 ]. The lack of differences in other dimensions of Utu by gender and orphan study resonate with the philosophical underpinnings of Utu that holds humanness as essential and protected irrespective gender, race, tribal, religious or political affiliations [ 72 ].…”
Section: Discussionsupporting
confidence: 93%
“…Interestingly, male caregivers only reported financial stressors. While it is possible that they did not experience physical or personal impacts of their caregiving role, it may also be due to discomfort in reporting such issues, as in Pakistani culture men are expected to be strong and any sign of weakness can lead to humiliation and mockery (Akram et al, 2015 ; Aqeel et al, 2019 ). While discussing confidence levels among caregivers, it was evident that male caregivers appeared to be more confident and assertive in their caregiving abilities.…”
Section: Discussionmentioning
confidence: 99%
“…While discussing confidence levels among caregivers, it was evident that male caregivers appeared to be more confident and assertive in their caregiving abilities. This again needs to be considered in the Pakistani context, where males are considered an authority figure and children fear their authority (Alvi et al, 2017 ; Aqeel et al, 2019 ). Although there was a range of experience, none of the caregivers had received any relevant prior professional training.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These skills enable effective communication, collaboration, and knowledge management (McKay and Avery, 2015). EI in HC is supported by intellectual capital literature (Aqeel et al, 2019). Emotional intelligence helps intellectual capital flourish, according to study.…”
Section: Literature Reviewmentioning
confidence: 99%